Sistem Informasi Penjualan Barang dan Jasa pada Studio Photo Topaz Hexagon Medan Berbasis Web - Sembiring, Josephine Oktavira; Ginting, Wasit (MEANS (Media Informasi Analisa dan Sistem), 2018)
Sales information system in Hexagon Medan Topaz Photo Studio is web-based to process the sales system that occurs, process multiple reports, provide up-to-date information about the photo studio and product products provided. With the information system on the sale of goods and services in the topaz hexagon field photo studio, it is expected to simplify and speed up the processing of data and information in the Topaz Hexagon Photo Studio in Medan. And can produce data and information on the results of sales activities that occur and produce accountability reports more quickly and practically. The system built is easy to learn by users (users) and the programming language used is PHP and MySQL to create a database